Congos de milagres: música, movimento e corporeidade em devoção à Nossa Senhora do Rosário - Raimundo Nonato Cordeiro (2014)
This work intends to produce a reflection on the Congos de Milagres, a celebration from Ceará Cariri performed as a form of devotion to Our Lady of Rosary. The objective of this research is to analyze the performance of players to interpret music, motion and body interaction as a meaning of expressing their complete devotion. Ethnography was the model used for the research, being the fieldwork the predominant instrument for the data collection. The theoretical basis was the ethnoscenology, where concepts such as spectacularity and thinking body, methodological assumptions applicable to the study of the organization of action and space depending on the look of the other person mediated by a body that produces and interprets meanings were employed. Based on indications native, was shown how to the dance steps are developed, was presented a proposed structuring of performance, was indicated how bodily experiences are crucial to the acquisition of the ability to perform the dance and exhibited the devotional motivation that keeps alive the manifestation.